China’s Foreign Policy towards Sri Lanka: An Economic Approach to Sustainable Development - Rahman, Md. Sayedur (Academia Journal of Humanities & Social Sciences, 2025)
China's expanding investment, trade, and assistance linkages are widely seen as a powerful tool of statecraft, creating significant security externalities. However, there is a scarcity of research establishing the specific processes that relate economic links between "sender" and "target" states to a genuine security influence. Sri Lanka's relations with India are hampered by weak infrastructure design and implementation, local politics and regional competitors, and emerging powers, with the ability to transform Beijing's vast economic resources into Sri Lanka strategically. Many potential areas of cooperation could prosper together if both friendly countries utilize them. This paper identified several possible areas of cooperation and argued that to attain sustainable development, Sino-Sri Lanka relations need to be strengthened more and more. This study explored the potential areas through various channels for greater interest, friendship, and opening up a new era in bilateral issues. This study examines and investigates the difficulties and prospects for enhancing economic relations between China and Sri Lanka. This study included both primary and secondary sources. This study based on the secondary sources of information and data, including academic journals, scholarly texts, research papers, articles, investigative papers, books, and other relevant materials are examples of secondary sources. Primary data was used in the trade data. Although the qualitative and quantitative methodologies were employed in the analysis, the quantitative approach was frequently used to make the study more transparent. At the end of this paper, some policy suggestions or recommendations are provided for the economic relationship between China and Sri Lanka. The study recommends a wide range of factors including bilateral treaties, free economic zones, joint ventures, improving microeconomic policy, reducing bureaucracy, and corruption, pursuing competitive advantage policy and working jointly to solve regional and global problems to promote Sino-Sri Lanka trade relations. This study is necessary, timely and significant for a better understanding of Chinese foreign policy towards Sri Lanka.